واقع سوق التامين واعادة التامين بالجزائر خلال 2010/2020 - فيصل, غنادرة (جامعة الوادي - University of Eloued, 2023)
"ملخص تعترب عمليات إعادة التأمني يف جمال التأمينات العامة وسيلة من وسائل العالج اليت ميكن من خالهلا دعم األمهية االقتصادية للتأمينات العامة عن طريق عدم تعرض املراكز املالية لشركات التأمني املباشر هلزات مالية عنيفة قد تؤدي إىل وقف النشاط وعدم استقراره خاصة بالنسبة لألخطار املركزة العالية القيمة، مما يؤدي إىل التأثري السليب على خطط التنمية االقتصادية من خالل إضعاف الدور االقتصادي اهلام للتأمني. هتدف هذه الدراسة إىل حتليلل واقلس سلإع إعلادة التلأمني يف ا زائلر ملن خلالل دراسلة النشلاط التقلر للشلركة املركزيلة إلعلادة التلأمني CCR خالل الفرتة )2002-0202( حيث قمنا بتحليل رقم أعمال الشركة وكذا حتليل حجلم املطالبلات أو التعإيتلات املدةإعلة سلإ اإلمجاليلة أو حسلف ةلروأ التلأمني، وقلد تإصلل الدراسلة إىل أن لنشلاط إعلادة التلأمني يف ا زائلر يف حتسلن مسلتمر هلذا التحسن ترجم حبجم األقساط احملصلة، حيث بلغ سنة 0202 مبلغ 1.0 مليار دينار، يف حلني بلغل سلنة 0202 مبللغ 33.1 مليار دج. كذلك يساهم نشاط إعادة التامني يف تغطية األخطار وهذا من خالل حجم التعإيتات املعتربة واملسددة يف إطار تعإيض احلإادث حيث بلغ التعإيتات خالل سنإات الدراسة )0202/0202( مبلغ 40.9 مليار دج ويعترب هذا املبلغ جد معترب وهإ يبني ويربز املسامهة الفعالة للشركة املركزية إلعادة التأمني CCR""Abstract: Reinsurance operations in the field of general insurance are considered as a means of treatment through which the economic importance of general insurance can be supported by not exposing the financial positions of direct insurance companies to violent financial shocks that may lead to the cessation of activity and its instability, especially with regard to high- value concentrated risks, which leads to The negative impact on economic development plans by weakening the important economic role of insurance. This study aims to analyze the reality of the reinsurance market in Algeria by studying the technical activity of the Central Reinsurance Company (CCR) during the period (2010-2020), where we analyzed the company's turnover, as well as analyzing the volume of claims or compensation paid except for the total or according to the insurance branches. The study indicated that the reinsurance activity in Algeria is constantly improving. This improvement was translated into the volume of premiums collected, as the year 2010 amounted to 6.1 billion dinars, while in 2020 it amounted to 33.6 billion dinars. Reinsurance activity also contributes to covering risks, and this is through the volume of compensation considered and paid within the framework of accident compensation, as compensation during the study years (2010/2020) amounted to 92.4 billion DZ"
ماستر اقتصاد
Keywords: ا زائر، الشركة املركزية إلعادة التأمني، إعادة التأمني، رقم األعمال، التعإيتات.; Algeria, Central Reinsurance Company, reinsurance, turnover, compensation.